The Effects of Different Phase on Independent Visual Fields SSVEP Responses - Dalu Zheng; Songyun Xie; Xinzhou Xie; Michael Scholz; Hao Tang (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Binocular disparate stimulation based on steady-state visual evoked potentials (SSVEP) generates more recognizable features but also introduces complexity hardening the interpretability of SSVEP responses. The individual contribution of each visual pathway when stimulating parts of the visual field remains unclear and is further obfuscated by the large spatial integration of EEG systems. We propose “independent visual field stimulation” (IVFS), utilizing a head-mounted display (HMD) as a novel experimental paradigm to improve the interpretability of SSVEP responses. By stimulating only half of the visual field and “coding” the stimulus further with different phases individual contributions of pathways and eyes can be easily separated and thus the mode of action becomes clearer. In a first proof-of-principles study on 15 subjects we demonstrate that IVFS with a 180° phase difference causes left and right scalp SSVEPs to exhibit a similar phase difference, and the propagation mechanism of SSVEPs conforms to the standing wave mode. Stimulating ipsilateral or contralateral pathways individually does influence temporal information processing but not SSVEP amplitudes. Utilizing the phase of the stimulus in addition to its frequency creates a new dimension and thus helps significantly to overcome frequency limitations in SSVEP research which otherwise dramatically hinder the read-out due to the prominent lowpass nature of the human head.